(untitled) (Fiep Bulletin - online, 2014)
This paper has the objective identify the body in risk at Deborah Colker´s dance. We analyzed the video Mix (2000), a join of some choreographies of the show “Vulcão” an “Velox”, with a especial attention to the Alpinism choreography, in which dancers use the stage in a vertical position, which desire of amplitude, elevation, these bodies try to frustrate the gravity phenomenon, to climb until the higher point of the unique creation. The study is imperative, with a qualitative role, presenting as investigation field the contemporary dance company by Deborah Colker. We concluded that the body in risk constructed in a esthetic production and beauty on the at the contemporary dance shoes by Deborah Colker with her dancers, is a different social practice that involves risk, normally at the contemporary times, that makes use of risk-adventure, concept for a positive risk, as an important moving of the modern senses of risk, in which brings back adventure as a positive dimension of risk, also called desired risk, where pleasure comes from the concretized objective